2020
DOI: 10.1073/pnas.2002981117
|View full text |Cite
|
Sign up to set email alerts
|

Mirrored brain organization: Statistical anomaly or reversal of hemispheric functional segregation bias?

Abstract: Humans demonstrate a prototypical hemispheric functional segregation pattern, with language and praxis lateralizing to the left hemisphere and spatial attention, face recognition, and emotional prosody to the right hemisphere. In this study, we used fMRI to determine laterality for all five functions in each participant. Crucially, we recruited a sample of left-handers preselected for atypical (right) language dominance (n= 24), which allowed us to characterize hemispheric asymmetry of the other functions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 61 publications
5
50
1
Order By: Relevance
“…This relationship points towards a general laterality factor which influences lateralisation across tasks and behaviours, as predicted by several theoretical accounts (Behrmann & Plaut, 2015;Hellige, 1993;Kosslyn, 1987). In a study of left-handers using fMRI with five tasks, Gerrits, Verhelst, and Vingerhoets (2020) found that the just under half the participants showed either standard laterality (left-lateralised for language and praxis, right-lateralised for face memory, line-bisection and vocal emotion) or a complete reversal of this pattern, providing clear evidence against the idea that these functions are lateralised independently. It is also clear that this association is far from perfect, (Badzakova-Trajkov, Haberling, Roberts, & Corballis, 2010) and some studies have found no correlation between laterality indices (Bryden, Hecaen, & Deagostini, 1983;Rosch, Bishop, & Badcock, 2012;Whitehouse & Bishop, 2009;van der Haegen & Brysbaert, 2018).…”
Section: Behavioural Laterality Tasks and (A)typical Lateralisationmentioning
confidence: 66%
See 1 more Smart Citation
“…This relationship points towards a general laterality factor which influences lateralisation across tasks and behaviours, as predicted by several theoretical accounts (Behrmann & Plaut, 2015;Hellige, 1993;Kosslyn, 1987). In a study of left-handers using fMRI with five tasks, Gerrits, Verhelst, and Vingerhoets (2020) found that the just under half the participants showed either standard laterality (left-lateralised for language and praxis, right-lateralised for face memory, line-bisection and vocal emotion) or a complete reversal of this pattern, providing clear evidence against the idea that these functions are lateralised independently. It is also clear that this association is far from perfect, (Badzakova-Trajkov, Haberling, Roberts, & Corballis, 2010) and some studies have found no correlation between laterality indices (Bryden, Hecaen, & Deagostini, 1983;Rosch, Bishop, & Badcock, 2012;Whitehouse & Bishop, 2009;van der Haegen & Brysbaert, 2018).…”
Section: Behavioural Laterality Tasks and (A)typical Lateralisationmentioning
confidence: 66%
“…Given the range of evidence now available, it may be time to abandon hypotheses that predict that different lateralised skills are either wholly interdependent or wholly independent. Evidence such as that from Gerrits et al (2020) confirms that lateralisation of different functions is associated far more than expected by chance, yet cases of dissociation are not uncommon. Research in future might explore which functions are associated, and to what extent, rather than making a simple contrast between models that postulate a general answer to explain all of laterality.…”
Section: Discussionmentioning
confidence: 88%
“…Recent research has revealed the crowded phenotype, where both motor and social abilities are dominant to the same side (left or right), to be the second most frequent functional brain organisation with the reversed template (where motor is right hemisphere dominant and social processing is left hemisphere dominant) to be the least represented 36,46 . This may seem contrary to comparative research and evolutionary theory, which would predict that the standard and reversed phenotypes would be most advantageous for efficient behaviour because each hemisphere is dominant for a primary survival function, regardless of side.…”
Section: Directional Motor Phenotypes Pegboard and Cradling Results mentioning
confidence: 99%
“…There have been recent discussions in the review literature suggesting that a standard functional brain organisation template is expressed by the majority of the population and is associated with typical cognition, while disruption to the standard template 'results in crowding' or reversal of the standard template. Although crowding does not appear to have significant cognitive implications, reversal is associated with decreased cognitive ability 36,46 . This is consistent with the comparative literature but lacks a narrative of causal origin.…”
Section: Directional Motor Phenotypesmentioning
confidence: 98%
“…With the aim of increasing the likelihood of identifying people with RLD, we limited the inclusion for our study to left-handers only as it has been shown that RLD is more likely to occur in left-handers (15% to 34% of left-handers compared to only 4% to 14% of right-handers (Carey & Johnstone, 2014;Knecht et al, 2000)). Details of the recruitment procedure and the classification of the participants as RLD or left language dominance (LLD) based on an fMRI word generation task are documented elsewhere (Gerrits et al, 2020). The sample consisted of 24 participants with RLD and 39 with LLD.…”
Section: Participantsmentioning
confidence: 99%